Development of friction-induced triboluminescent sensor for load monitoring - Shohag, Md Abu S; Jiang, Zhengqian; Hammel, Emily C; Braga Carani, Lucas [UNESP]; Olawale, David O; Dickens, Tarik J; Wang, Hui; Okoli, Okenwa I (SAGE Publications, 2018)
Real-time load monitoring of critical civil and mechanical structures especially dynamic structures such as wind turbine blades is imperative for longer service life. This article proposed a novel sensor system based on the proprietary in situ triboluminescent optical fiber (ITOF) sensor for dynamic load monitoring. The new ITOF sensor patch consists of an ITOF sensor network with micro-exciters integrated within a polymer matrix. The sensor patch was subjected to repeated flexural loading and produced triboluminescent emissions due to the friction between micro-exciters and ITOF sensors corresponding to each loading cycle. The friction-induced triboluminescent intensity directly depends on the loading rate, the coefficient of friction, and the applied load on patch. In general, the triboluminescent intensity increases exponentially with an increase in load. Additionally, the sensor patches comprising the coarser micro-exciters exhibited better results. Similarly, better results were achieved at higher loading rates although a threshold loading rate is required to excite the triboluminescent crystals for this sample configuration. The proposed new sensor has the ability to monitor dynamic continuous applied loads.
Keywords: flexural loading; friction; load monitoring; sensor; sensor patch; Triboluminescence